A novel brace with partial buckling restraint: An experimental and numerical investigation. (1st November 2017) - Wang, Chun-Lin; Chen, Quan; Zeng, Bin; Meng, Shaoping
Highlights: A novel brace with partial buckling restraint was proposed for the visual inspection. In the PBRB, only the edge parts of the core member are restrained. The unrestrained ratio of the unrestrained part is one key parameter. The PBRB with lower fatigue properties is still acceptable. Failure mode of PBRB with a small unrestrained ratio is similar to the BRB. Abstract: For the immediate damage evaluation of a buckling-restrained brace (BRB) after earthquakes, a novel brace with partial buckling restraint was proposed. In the novel brace called the partially buckling-restrained brace (PBRB), only the edge parts of the core member are restrained, and the middle portion of the core member, the unrestrained part, is designed for visual inspection. This paper focuses on the partial restraining mechanism of the PBRB, and three PBRB specimens were tested and compared with two conventional BRB specimens. The unrestrained ratio of the width of the unrestrained part to the thickness of the same part was studied as one of the key parameters that affects the behaviour of the PBRB. Even if the PBRB shows relatively lower fatigue properties and higher compression strength adjustment factors compared with the conventional BRB, the behaviour of the PBRB is still acceptable. The PBRB with a large unrestrained ratio fails at the end of the yielding core plate, where the unrestrained buckling deformation of the core plate is significant, but the fracture of the PBRB with a small unrestrained ratio occurs around the stopper, similar to the failure mode of the BRB. Numerical results show that the maximum plastic strain concentrates in the wave valley of the ends of the yielding core plate for the PBRB with the large unrestrained ratio. To make sure that the behaviour of the PBRB is comparable to that of the conventional BRB, it is recommended that the unrestrained ratio should be less than 5.